The place of the cultural and natural sights of countries of the CIS in List of world heritage of UNESCO - Комаренко О.; Василенко В. (Київський національний університет імені Тараса Шевченка, 2009)
Analyzing the Convention concerning the protection of the world cultural and natural heritage UNESCO, the author studies the place of the cultural and natural sights of countries of the CIS in List of world heritage of UNESCO

На основі аналізу Конвенції про охорону всесвітньої культурної і природної спадщини ЮНЕСКО досліджено місце культурних і природних пам'яток у Списку всесвітньої спадщини ЮНЕСКО.
Місце культурних та природних пам'яток країн СНД у Списку всесвітньої спадщини ЮНЕСКО